Taḥlīl akhṭā’ al-af‘āl al-kalāmiyyah bi markaz tarqiyah al-lughah al-ajnabiyyah ma‘had Dār al-Lughah wa al-Karāmah Kraksaan Probolinggo: تحليل أخطاء الأفعال الكلامية بمركز ترقية اللغة الأجنبية معهد دار اللغة و الكرامة كركسان بروبولمجو - Sulton Firdaus; Bintang Ramadhan; Erma Suriani; Moh Nasikin (Cordova Journal, 2026)
This study aims to describe and analyze the types of errors in speech acts in the use of everyday Arabic at the Foreign Language Development Center of Dar al-Lughah wa al-Karamah Institute, Kraksaan, Probolinggo. The study focuses on pragmatic errors that emerge in students’ interactions outside the classroom, including directive speech acts (requests, commands), expressive acts (gratitude, apologies), commissive acts (promises), and representative acts (statements).The findings reveal four main patterns of errors: (1) the use of grammatically correct structures that are inappropriate for the social context (e.g., giving direct commands to seniors), (2) the use of overly direct speech acts perceived as impolite (e.g., using “a‘ṭinī” [give me] without a politeness marker), (3) errors in selecting culturally appropriate expressive forms (e.g., insincere or exaggerated expressions of thanks or apology), and (4) code-mixing with Indonesian or Javanese/Madurese, which disrupts the coherence of speech acts. The main contributing factors include pragmatic interference from the mother tongue, a lack of deep understanding of politeness norms in Arab culture, and limited exposure to authentic interactions with native speakers. This study recommends integrating explicit instruction on pragmatics and cross-cultural politeness into the curriculum of the Foreign Language Development Center, as well as increasing the use of simulations of real social contexts in learning.